ANALISIS STRUKTUR EKONOMI DAN IDENTIFIKASI SEKTOR - SEKTOR UNGGULAN DI KOTA PALU - Tenggara, Ady Putra (Katalogis, 2015)
Based on the analysis of LQ, in addition to eight other sectors of agriculture sector is a sector basis should be developed and given special attention so that the sector remains a sector basis in the future. While based on the analysis of the SS and the sector needs to be developed not only into sectors that have a comparative advantage but has a value of competitive advantage, the sector is the building sector, sector of trade, hotels and restaurants, as well as the financial sector, leasing and other services. These results are in line with the results of using MRP calculation (RPs) and overlay analysis. Based on the results of MRP (RPs), industrial, construction, trade, hotels and restaurants, as well as finance, leasing and services. To the four sectors have a value of more than 1, or RPs>1. The value of the sector is 1.30 kempat industry sector, sector dangunan 1.10, 1.25 trade, hotels and restaurants, as well as the 1.02 finance, leasing and services. While based overlay analysis, consists predominantly of the processing industry sector, construction sector, trade, hotels and restaurants sector and the financial sector, leasing and services. Currently consisting of negative sector is the sector of quarrying, electricity and water supply, transport and communication sectors, as well as the services sector. As well as sectors that are not potential is agriculture.